The Role of Air Pollution and Olfactory Dysfunction in Alzheimer’s Disease Pathogenesis - Louise Odendaal; Hazel Quek; Carla Cuní-López; Anthony R. White; Romal Stewart (Biomedicines)
The escalating issue of air pollution contributes to an alarming number of premature fatalities each year, thereby posing a significant threat to global health. The focus of recent research has shifted towards understanding its potential association with neurodegenerative diseases, specifically Alzheimer’s disease (AD). AD is recognised for its characteristic deposition of toxic proteins within the brain, leading to a steady deterioration of cognitive capabilities, memory failure, and, ultimately, death. There is burgeoning evidence implying that air pollution may be a contributing factor to this protein build up, thereby intensifying the course of AD. It has been demonstrated that the olfactory system, responsible for smell perception and processing, acts as a potential gateway for airborne pollutants to inflict brain damage. This review aims to elucidate the relationship between air pollution, olfactory deterioration, and AD. Additionally, this review aims to highlight the potential mechanisms through which pollutants might instigate the development of AD and the role of the olfactory system in disease pathogenesis. Moreover, the diverse model systems employed in exploring the correlation, public health policy ramifications, and prospective directions for future research will be discussed.